The Authoritative Sway of Artificial Boundaries of Sexual Orientation: An Ethical Imperative for Public Administration. (2nd November 2021) - DiPadova-Stocks, Laurie N.; Ehrlich, Donna M.; Cowley, Brian J.
Abstract : Public administrators implement and direct the powers of government. Public administration ethics, combined with social equity, is positioned to direct these powers and to thereby advance the rights and inclusion of all humanity. This paper discusses how social categories create artificial boundaries and allow for authoritative removal of rights; it examines barriers to full rights and privileges for individuals who are LGBT. We ask: Do public administration ethics reflect the self-evident truths of the founding documents, including "all… are created equal" with "unalienable rights?" Unfortunately, "all" still does not apply to everyone. Today some groups remain marginalized. Centuries after the Constitution was ratified, in the wake of WWII, the international community affirmed our founding principles. Do we limit rights through categories we create? In society are we "man" or "woman" only as a result of categories determined by various religious approaches? Employing intersectionality and Critical Action Research, we draw from stories of students who are LGBT. We surface the damaging impacts of negative categorization, stigma, and hierarchy of credibility which contribute to their experience as "lesser" persons in society. We conclude with expanding social equity in a way to extend ethics in Public Administration to Humanity Beyond Boundaries.